2020
DOI: 10.21070/jbmp.v6i2.822
|View full text |Cite
|
Sign up to set email alerts
|

Competencies and Service Quality of a Private Non-Sectarian University In Cebu City, Philippines

Abstract: This study was to determine the competencies and service quality of government employees teaching part-time at the university. The study collected data on the assessment of the teachers about skills and students regarding the service quality of their teachers in a private non-sectarian university in Cebu City, Philippines. The part-time teachers in the university have extremely high competencies in methodology, motivation, material utilization, instructional process, teaching evaluation, and interaction proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The findings of Seth (2022) also revealed that perceived integrity in leadership directly affects employees' trust in leaders and organizational commitment. As regards service which appears to be directly influenced by the work environment and engagement and work-life balance, the findings of John (2023), Hafeez, et al (2019), Akunne, et al (2022, Astillero et al, (2020) agree on the likelihood that satisfied employees with good work environment will develop a sense of commitment and service towards the organization. This is because the work environment is perceived to be of the most important components influencing employee performance.…”
Section: Figure 2 Structural Modelmentioning
confidence: 99%
“…The findings of Seth (2022) also revealed that perceived integrity in leadership directly affects employees' trust in leaders and organizational commitment. As regards service which appears to be directly influenced by the work environment and engagement and work-life balance, the findings of John (2023), Hafeez, et al (2019), Akunne, et al (2022, Astillero et al, (2020) agree on the likelihood that satisfied employees with good work environment will develop a sense of commitment and service towards the organization. This is because the work environment is perceived to be of the most important components influencing employee performance.…”
Section: Figure 2 Structural Modelmentioning
confidence: 99%